Application features of indicators to assess competitiveness of products in modern conditions - Niyazbekova, R.K.; Oguz , Durru (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the competitiveness of goods depending on the intended and specific goals of competitiveness. The authors used two groups of features: technical indicators of quality and economic parameters. According to the authors, the technical parameters of the goods consist of parameters, requirements (assigned, ergonomic, aesthetic, and normative), characterizing the content quality needs and conditions of its satisfaction. The article stated that the calculation of the integrated indicator on economic parameters is based on determining the completeness of the costs of consumer acquisition and usage of the goods. The authors determined requirements to an assessment of competitiveness of goods: market research, study of competitors’ products, study customer requirements, determination of evaluation parameters of goods, classification of factors of competitiveness of goods, determination of methods of a quantitative estimation of competitiveness of goods. The article systematically grouped and classified, the process indicators to assess the competitiveness of goods: a group of indicators, reflecting the progressivity of the commercial idea of the goods; the group of technical, economic and commercial indicators of the quality of the products; a group of indicators that characterize the conditions of the sale; the group of indicators describing the conditions of use; the group of indicators characterizing socio-psychological acceptance of products by the consumer. The authors made specific findings in terms of determining the competitiveness of goods.